Smart System Farming Management: Exposure Fintech Bumdes Dalam Memperkuat Ketahanan Ekonomi Pada Sektor Pangan - Thoriqi Firdaus; Farah Lailatul Nur Alifiyah; Ainunnuril Amelia (Journal of Food Industrial Technology, 2024)
Agriculture contributes significantly to food security and economic growth. A system for managing agriculture that is smart and based on financial capital and technology is needed to increase agricultural profits again. This research uses a mixed method with a sequential explanatory design, namely a causal-comparative study, and a grounded theory approach. Based on the results of multivariate statistical analysis tests, there are differences between traditional and modern farmers. Conventional and contemporary farmers have the same problems: lack of motivation to farm and insufficient availability of agricultural materials. The differences in farming capital, management and control, labor, and profits from farm products. Farmers need a system that can maximize agricultural yields by creating smart agriculture. This concept can be realized in a smart farming management system to control all pre-planting to post-harvest activities based on BUMDes fintech. Financial limitations make this fintech-based smart farming management system capable of being an alternative solution implemented in a hybrid manner so that all farmers can utilize it. Five features are available on the smart farming platform: information features, procurement of agricultural tools and materials, monitoring, and sales of farm and agricultural products. The advantages of a smart farming management system are increasing the productivity of farm products, improving the welfare of farmers, stabilizing market prices, improving the quality of agricultural products, opening up employment opportunities, and promoting agricultural products so that they have the potential to improve the socio-economic conditions of village communities.